The Effect of Carbon Emission Disclosure, Green Accounting, Leverage on Company Performance with Firm Age as a Moderating Variable in Energy Sector Companies in Indonesia 2021-2023 - Jessica Hutarso; Regina Jansen Arsjah (Utan Kayu Publishing, 2025)
This study aims to prove the impact of carbon emission disclosure, green accounting and leverage on firm performance in energy companies in Indonesia; and to verify whether firm age moderates the effect of green accounting, carbon emission disclosure and leverage on firm performance. This research was conducted by analyzing information from companies engaged in the energy sector in 2021 to 2023, in Indonesia and listed on the Indonesia Stock Exchange (IDX). This study uses a descriptive analysis method with a quantitative approach, where this study aims to describe and explain phenomena that occur factually based on data based on numbers and statistics. Analysis of this study shows that carbon emission disclosure, green accounting and leverage are not proven to have a positive effect on company performance in energy companies in Indonesia from 2021 to 2023. Meanwhile, firm age is proven to moderate (strengthen) the positive effect of Carbon Emission Disclosure, Green Accounting and Leverage on Company Performance.